Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Dynamic benthic oxygen fluxes lessen hypoxia effects on open continental shelves - Clare E. Reimers; Sarah K. Henkel; Kristen E. Fogaren; Peter J. Chace; Anna Hughes; W. Waldo Wakefield (Limnology and Oceanography, 2025)
Under the supposition that organisms inhabiting physically dynamic marine environments are better able to survive hypoxic conditions than those experiencing little turbulent or advective augmentation of oxygen fluxes, we evaluated summertime benthic macrofauna communities, in situ aquatic eddy covariance measurements, and ex situ sediment core incubations from 5 latitudinally distinct mid‐shelf locations off Oregon–Washington, USA. Despite bottom water dissolved oxygen (DO) concentrations averaging from 17 to 75 μ mol L −1 , invertebrate faunal collections contained mixtures of 11 to 28 taxa per 0.1 m 2 box core and increased in richness and abundance at sites with greater velocity variation. Eddy covariance velocity records of 18‐30 hours regularly showed the arrivals of internal waves. Oxygen fluxes, derived in 15‐min intervals, correlated with multiple flow parameters assessed from velocity components. Daily averages of the oxygen fluxes to the sediment were determined to range from −3.5 to −23 mmol m −2 d −1 , and these fluxes, assumed to fully represent seabed respiration, were 2 to 5 times greater than rates of DO uptake by sediment cores from the same locations. Velocity profiles measured from 0.3 to 2.5 m above the seafloor at a subset of sites were consistent with a wave‐current boundary layer modulated by ocean swell. These findings illustrate how natural physical processes can relieve the stress of hypoxia exposure on the benthos. Physical dynamics play critical roles in supplying DO and determining sediment grain size, permeability, and the activities of benthic organisms. Thus, these factors need consideration when predicting the impacts of low DO concentrations in coastal regions.

Bloom compression alongside marine heatwaves contemporary with the Oregon upwelling season - Ian T. Black; Maria T. Kavanaugh; Clare E. Reimers (Limnology and Oceanography, 2025)
Marine heatwave (MHW) events have led to acute decreases in primary production and phytoplankton biomass in the surface ocean, particularly at the mid latitudes. In the Northeast Pacific, these anomalous events have occasionally encroached onto the Oregon shelf during the ecologically important summer upwelling season. Increased temperatures reduce the density of offshore waters, and as a MHW is present offshore, coincident downwelling or relaxation may transport warmer waters inshore. As an event persists, new upwelling‐driven blooms may be prevented from extending further offshore. This work focuses on MHWs and coincident events that occurred off Oregon during the summers of 2015–2023. In late summer 2015 and 2019, both documented MHW years, coastal phytoplankton biomass extended on average 6 and 9 km offshore of the shelf break along the Newport Hydrographic Line, respectively. During years not influenced by anomalous warming, coastal biomass extended over 34 km offshore of the shelf break. Reduced biomass also occurs with reduced upwelling transport and nutrient flux during these anomalous warm periods. However, the enhanced front associated with a MHW aids in the compression of phytoplankton closer to shore. Over shorter events, heatwaves propagating far inshore also coincide with reduced chlorophyll a and sea‐surface density at select cross‐shelf locations, further supporting a physical displacement mechanism. Paired with the physiological impacts on communities, heatwave‐reinforced physical confinement of blooms over the inner‐shelf may have a measurable effect on the gravitational flux and alongshore transport of particulate organic carbon.

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

Corrigendum to “Spatiotemporal variability in benthic-pelagic coupling on the Oregon-Washington Shelf” [Marine Chemistry Volume 268 (2025) Article number 104473] - Anna Hughes; Clare E. Reimers; Kristen E. Fogaren; Yvan Alleau (Marine Chemistry, 2025)

Spatiotemporal variability in benthic-pelagic coupling on the Oregon-Washington shelf - Anna Hughes; Clare E. Reimers; Kristen E. Fogaren; Yvan Alleau (Marine Chemistry, 2025)

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

The role of seasonal hypoxia and benthic boundary layer exchange on iron redox cycling on the Oregon shelf - Natalya Evans; Alexis E. Floback; Justin Gaffney; Peter J. Chace; Zachary Luna; Joël Knoery; Clare E. Reimers; James W. Moffett (Limnology and Oceanography, 2024)
Widespread hypoxia occurs seasonally across the Oregon continental shelf, and the duration, intensity, and frequency of hypoxic events have increased in recent years. In hypoxic regions, iron reduction can liberate dissolved Fe(II) from continental shelf sediments. Fe(II) was measured in the water column across the continental shelf and slope on the Oregon coast during summer 2022 using both a trace metal clean rosette and a high‐resolution benthic gradient sampler. In the summer, Fe(II) concentrations were exceptionally high (40–60 nM) within bottom waters and ubiquitous across the Oregon shelf, reflecting the low oxygen condition (40–70 μM) at that time. The observed inverse correlation between Fe(II) and bottom water oxygen concentrations is in agreement with expectations based on previous work that demonstrates oxygen is a major determinant of benthic Fe fluxes. Rapid attenuation of Fe(II) from the benthic boundary layer (within 1 m of the seafloor) probably reflects efficient cross‐shelf advection. One region, centered around Heceta Bank (~ 44°N) acts a hotspot for Fe release on the Oregon continental shelf, likely due to its semi‐retentive nature and high percent mud content in sediment. The results suggest that hypoxia is an important determinant of the inventory of iron is Oregon shelf waters and thus ultimately controls the importance of continental margin‐derived iron to the interior of the North Pacific Basin.

Do contaminants compromise the use of recycled nutrients in organic agriculture? A review and synthesis of current knowledge on contaminant concentrations, fate in the environment and risk assessment - E.K. Bünemann; M. Reimer; E. Smolders; S.R. Smith; M. Bigalke; A. Palmqvist; K.K. Brandt; K. Möller; R. Harder; L. Hermann; B. Speiser; F. Oudshoorn; et al. (Science of The Total Environment, 2024)

Extremely 13C-enriched dolomite records interval of strong methanogenesis following a sulfate decline in the Miocene Ries impact crater lake - Lingqi Zeng; Jochen Gätjen; Manuel Reinhardt; Michael E. Böttcher; Andreas Reimer; Volker Karius; Volker Thiel; Gernot Arp (Geochimica et Cosmochimica Acta, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Phylogenomics of Palythoa (Hexacorallia: Zoantharia): probing species boundaries in a globally distributed genus - ‘Ale‘alani Dudoit; Maria E. A. Santos; James D. Reimer; Robert J. Toonen (Coral Reefs, 2022)

Same but different? Zoantharian assemblages (Anthozoa: Hexacorallia) in Bonaire and Curaçao, southern Caribbean - James Davis Reimer; Hin Boo Wee; Jaaziel E. García-Hernández; Bert W. Hoeksema (Coral Reefs, 2022)

Noise can create or erase long transient dynamics - J. R. Reimer; J. Arroyo-Esquivel; J. Jiang; H. R. Scharf; E. M. Wolkovich; K. Zhu; C. Boettiger (Theoretical Ecology, 2021)

Insights Into Sea Turtle Population Composition Obtained With Stereo-Video Cameras in situ Across Nearshore Habitats in the Northeastern Gulf of Mexico - Tabitha Siegfried; Christopher Noren; Jackson Reimer; Matthew Ware; Mariana M. P. B. Fuentes; Susan E. Piacenza (Frontiers in Marine Science, 2021)
Population size estimates are key parameters used in assessments to evaluate and determine a species’ conservation status. Typically, sea turtle population estimates are made from nesting beach surveys which capture only hatchling and adult female life stages and can display trends opposite of the full population. As such, in-water studies are critical to improve our understanding of sea turtle population dynamics as they can target a broader range of life stages – though they are more logistically and financially challenging to execute compared to beach-based surveys. Stereo-video camera systems (SVCS) hold promise for improving in-water assessments by removing the need to physically capture individuals and instead extract 3D measurements from video footage, thereby simplifying monitoring logistics and improving safety for the animals and surveyors. To demonstrate this potential, snorkel surveys were conducted at artificial habitats in the northeastern Gulf of Mexico (neGOM) to collect size and photo-identification data on sea turtles in situ using a SVCS. Over 29.86 survey hours, 35 sea turtles were observed across three species ( Caretta caretta, Chelonia mydas , and Lepidochelys kempii ) and all neritic life stages (juvenile, sub-adult, and adult) utilizing different habitats, including artificial reefs, jetties, and fishing piers. Greens straight carapace length ranged from 28.55 to 66.96 cm ( n = 23, mean 43.07 cm ± 11.26 cm standard deviation; SD) and loggerheads ranged from 59.71 to 91.77 cm ( n = 10, mean 74.50 cm ± 11.35 cm SD), and Kemp’s ridleys ranged from 42.23 cm to 44.98 cm (mean 43.61 cm ± 1.94 cm SD). Using a linear mixed model, we found that species and habitat type were the most important predictors of sea turtle body length distribution. Overall, this case study demonstrates the potential of SVCS surveys to enhance our understanding of the population structure of sea turtle species within the neGOM and elsewhere.

An integrative approach reveals a new species of Zoantharia (Cnidaria, Anthozoa), Terrazoanthus silveirai , in the South-western Atlantic Ocean - Claudia F. Vaga; Alvaro E. Migotto; Maria E. A. Santos; Renato M. Honji; James Reimer; Marcelo V. Kitahara (Marine Biology Research, 2021)

Dopamine D2 receptors in the expression and extinction of contextual and cued conditioned fear in rats - Vivian M. de Vita; Heloisa R. Zapparoli; Adriano E. Reimer; Marcus L. Brandão; Amanda R. de Oliveira (Experimental Brain Research, 2021)

Vigilance in reindeer (Rangifer tarandus); evolutionary history, predation and human interference - Eigil Reimers; Sindre Eftestøl; Jonathan E. Colman (Polar Biology, 2021)
To elucidate genetic variability in vigilance behaviour for reindeer with historical differences in their interactions with predators and humans, we measured vigilance frequency and duration for grazing reindeer in Southern Norway (Rondane and Norefjell-Reinsjøfjell), Svalbard (Edgeøya and Nordenskiöld Land) and Barf/Royal Bay and Busen in the southern Hemisphere (South Georgia). Averaged for all areas, frequency and duration of vigilance bouts were less than 0.5 and 2.5 s, respectively. Frequency was insignificantly 1.3 times higher in Rondane than Edgeøya, and significantly 2.0, 3.5, 5.2 and 12.4 times higher than Norefjell, Nordenskiöld Land, Barf/Royal Bay and Busen, respectively. Duration per vigilance bout was not different amongst the areas. Thus, while frequency varied considerably, duration remained constant, supporting a hard-wired adaptation to, among other suggestions, an open landscape. Plasticity in frequency allows for flexible behavioral responses to environmental factors with predation, domestication and hunting key drivers for reindeer. Other factors include (1) the open, treeless alpine/Arctic environment inhabited by Rangifer subspecies allowing warning time, (2) grouping behaviour, (3) relative low density of predators and (4) the anatomy and physiology of ungulate vision.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Acidification in the U.S. Southeast: Causes, Potential Consequences and the Role of the Southeast Ocean and Coastal Acidification Network - Emily R. Hall; Leslie Wickes; Louis E. Burnett; Geoffrey I. Scott; Debra Hernandez; Kimberly K. Yates; Leticia Barbero; Janet J. Reimer; Mohammed Baalousha; Jennifer Mintz; Wei-Jun Cai; J. Kevin Craig; et al. (Frontiers in Marine Science, 2020)

Octocoral-associated Parazoanthus cf. swiftii from the southwestern Atlantic - Claudia F. Vaga; Maria E. A. Santos; Alvaro E. Migotto; James Reimer; Marcelo V. Kitahara (Marine Biodiversity, 2020)

Modeling optimal responses and fitness consequences in a changing Arctic - Jody R. Reimer; Marc Mangel; Andrew E. Derocher; Mark A. Lewis (Global Change Biology, 2019)
Animals must balance a series of costs and benefits while trying to maximize their fitness. For example, an individual may need to choose how much energy to allocate to reproduction versus growth, or how much time to spend on vigilance versus foraging. Their decisions depend on complex interactions between environmental conditions, behavioral plasticity, reproductive biology, and energetic demands. As animals respond to novel environmental conditions caused by climate change, the optimal decisions may shift. Stochastic dynamic programming provides a flexible modeling framework with which to explore these trade‐offs, but this method has not yet been used to study possible changes in optimal trade‐offs caused by climate change. We created a stochastic dynamic programming model capturing trade‐off decisions required by an individual adult female polar bear ( Ursus maritimus ) as well as the fitness consequences of her decisions. We predicted optimal foraging decisions throughout her lifetime as well as the energetic thresholds below which it is optimal for her to abandon a reproductive attempt. To explore the effects of climate change, we shortened the spring feeding period by up to 3 weeks, which led to predictions of riskier foraging behavior and higher reproductive thresholds. The resulting changes in fitness may be interpreted as a best‐case scenario, where bears adapt instantaneously and optimally to new environmental conditions. If the spring feeding period was reduced by 1 week, her expected fitness declined by 15%, and if reduced by 3 weeks, expected fitness declined by 68%. This demonstrates an effective way to explore a species' optimal response to a changing landscape of costs and benefits and highlights the fact that small annual effects can result in large cumulative changes in expected lifetime fitness.

Exploring the Biodiversity of Understudied Benthic Taxa at Mesophotic and Deeper Depths: Examples From the Order Zoantharia (Anthozoa: Hexacorallia) - James Davis Reimer; Hiroki Kise; Maria E. A. Santos; Dhugal John Lindsay; Richard L. Pyle; Joshua M. Copus; Brian W. Bowen; Masanori Nonaka; Takuo Higashiji; Yehuda Benayahu (Frontiers in Marine Science, 2019)

Germany’s 2018 report card on physical activity for children and youth - Yolanda Demetriou; Jens Bucksch; Antje Hebestreit; Annegret Schlund; Claudia Niessner; Steffen C. E. Schmidt; Jonas David Finger; Michael Mutz; Klaus Völker; Lutz Vogt; Alexander Woll; Anne K. Reimers (German Journal of Exercise and Sport Research, 2019)

Diversity of Saint Helena Island and zoogeography of zoantharians in the Atlantic Ocean: Jigsaw falling into place - Maria E. A. Santos; Peter Wirtz; Javier Montenegro; Hiroki Kise; Cataixa López; Judith Brown; James Davis Reimer (Systematics and Biodiversity, 2019)

Description of the juvenile form of the sea cucumber Thelenota anax H. L. Clark, 1921 - Taha Soliman; James D. Reimer; Iori Kawamura; Sancia E. T. van der Meij; Bastian T. Reijnen; Gustav Paulay (Marine Biodiversity, 2019)

Rangifer within areas of human influence: understanding effects in relation to spatiotemporal scales - Kjetil Flydal; Diress Tsegaye; Sindre Eftestøl; Eigil Reimers; Jonathan E. Colman (Polar Biology, 2019)

Zoantharia (Anthozoa: Hexacorallia) abundance and associations with Porifera and Hydrozoa across a depth gradient on the west coast of Curaçao - James Davis Reimer; Hin Boo Wee; Jaaziel E. García-Hernández; Bert W. Hoeksema (Systematics and Biodiversity, 2018)

Zooxanthellate zoantharians (Anthozoa: Hexacorallia: Zoantharia: Brachycnemina) in the northern Red Sea - James Davis Reimer; Javier Montenegro; Maria E. A. Santos; Martyn E. Y. Low; Marcela Herrera; Remy Gatins; May B. Roberts; Michael L. Berumen (Marine Biodiversity, 2017)

Latitudinal variation in the symbiotic dinoflagellate Symbiodinium of the common reef zoantharian Palythoa tuberculosa on the Saudi Arabian coast of the Red Sea - James D. Reimer; Marcela Herrera; Remy Gatins; May B. Roberts; John E. Parkinson; Michael L. Berumen (Journal of Biogeography, 2017)
Aim The Red Sea presents an ideal setting to explore the variability of Symbiodinium over environmental, latitudinal and geographical gradients. We used sequences from two molecular markers to examine genetic diversity of Symbiodinium associated with the widely distributed zoantharian Palythoa tuberculosa in the northern and central Red Sea. Location Northern and central Red Sea. Methods Specimens ( n = 329) were collected from 15 locations. Sequence data from nuclear ribosomal ITS 2 ( n = 269) and chloroplast minicircle psbA ncr ( n = 173) were phylogenetically analysed (maximum likelihood, neighbour joining), and Symbiodinium types identified for each P. tuberculosa colony. To establish whether environment was a strong predictor of Symbiodinium psbA ncr lineage, SST , chlorophyll‐ a , salinity, and depth data were fit into a multinomial logistic regression using the package VGAM in the R statistical environment. Results Based on ITS 2 and psbA ncr results, P. tuberculosa colonies were shown to be in symbioses with Symbiodinium clade C ( n = 172) and clade D ( n = 1). Within clade C, four psbA ncr lineages were observed; closely related lineages designated Pt‐1‐a and Pt‐1‐b, and closely related lineages Pt‐3‐a and Pt‐3‐b. By location, Pt‐1‐a dominated the sites within the Gulf of Aqaba ( c . 86%, 37/43 colonies). At the entrance to the Gulf of Aqaba, Pt‐3‐a dominated ( c . 88%, 15/17), while the more southern remaining sites in the Red Sea were dominated by Pt‐3‐b ( c . 78%, 89/113). Main conclusions Multinomial logistic regression analyses established that predictions based on the combination of temperature, chlorophyll‐ a and salinity accurately reflected symbiont distributions in the central and northern Red Sea. Palythoa tuberculosa host Pt‐1‐a in the coldest region, the Gulf of Aqaba (annual average SST = 24.5–25.0 °C), while immediately to the south Pt‐3‐a dominates ( SST = 26.0–26.5 °C), with warmest southern sites dominated by Pt‐3‐b ( SST > 26.5 °C). The Gulf of Aqaba is a unique environment, and more research on Symbiodinium outside the Gulf is required to understand symbiont diversity patterns within the Red Sea.

Dopamine D2-like receptors modulate freezing response, but not the activation of HPA axis, during the expression of conditioned fear - Amanda R. de Oliveira; Adriano E. Reimer; Fernando M. C. V. Reis; Marcus L. Brandão (Experimental Brain Research, 2017)

Sedimentology, structure and age estimate of five continental slope submarine landslides, eastern Australia - S. Clarke; T. Hubble; J. Webster; D. Airey; E. De Carli; C. Ferraz; P. Reimer; R. Boyd; J. Keene (Australian Journal of Earth Sciences, 2016)

Sponges hosting the zoantharia-associated crab Platypodiella spectabilis at St. Eustatius, Dutch Caribbean - J. E. Garcia-Hernandez; J. D. Reimer; B. W. Hoeksema (Coral Reefs, 2016)

The resurrection of the genus Bergia (Anthozoa, Zoantharia, Parazoanthidae) - Javier Montenegro; Martyn E. Y. Low; James Davis Reimer (Systematics and Biodiversity, 2016)

High-voltage power lines near wild reindeer calving areas - Jonathan E. Colman; Diress Tsegaye; Kjetil Flydal; Inger Maren Rivrud; Eigil Reimers; Sindre Eftestøl (European Journal of Wildlife Research, 2015)

Yellow tails in the Red Sea: phylogeography of the Indo‐Pacific goatfish Mulloidichthys flavolineatus reveals isolation in peripheral provinces and cryptic evolutionary lineages - Iria Fernandez‐Silva; John E. Randall; Richard R. Coleman; Joseph D. DiBattista; Luiz A. Rocha; James D. Reimer; Carl G. Meyer; Brian W. Bowen (Journal of Biogeography, 2015)
Aim Broadly distributed reef fishes tend to have high gene flow mediated by a pelagic larval phase. Here, we survey a reef‐associated fish distributed across half the tropical oceans, from the Red Sea to the central Pacific. Our goal is to determine whether genetic structure of the broadly distributed Yellowstripe Goatfish ( Mulloidichthys flavolineatus ) is defined by biogeographical barriers, or facilitated via larval dispersal. Location Red Sea, Indian Ocean, Pacific Ocean Methods Specimens were obtained at 19 locations from the Red Sea to Hawai'i. Genetic data include mt DNA cytochrome b ( n = 217) and 12 microsatellite loci ( n = 185). Analysis of molecular variance ( AMOVA ), structure , a parsimony network and coalescence analyses were used to resolve recent population history and connectivity. Results Population structure was significant (mt DNA ϕ ST = 0.68, P 0.001; microsatellite F ST = 0.08, P 0.001), but mostly driven by samples from the North‐western ( NW ) Indian Ocean (including the Red Sea) and Hawai'i. There was little population structure across the Indian Ocean to the central Pacific. Hawai'i was distinguished as an isolated population (mt DNA ϕ ST = 0.03–0.08, P = n.s.; microsatellites F ST = 0.05–0.10, P 0.001). Specimens from the NW Indian Ocean clustered as a distinct phylogenetic lineage that diverged approximately 493 ka ( d = 1.7%), which indicates that these fish persisted in isolation through several Pleistocene glacial cycles. Main conclusions These data reinforce the emerging themes that: (1) phylogeographical breaks within species often coincide with biogeographical breaks based on species distributions, and (2) populations on the periphery of the range ( NW Indian Ocean and Hawai'i) are isolated and may be evolutionary incubators producing new species.

A late Pleistocene–Holocene multi‐proxy record of palaeoenvironmental change from Still Bay, southern Cape Coast, South Africa - Lynne J. Quick; Andrew S. Carr; Michael E. Meadows; Arnoud Boom; Mark D. Bateman; David L. Roberts; Paula J. Reimer; Brian M. Chase (Journal of Quaternary Science, 2015)
The southern Cape is a key focus for southern African palaeoenvironmental research as it represents the transitional region between temperate westerlies and sub‐tropical rainfall sources. This study presents pollen, plant biomarker, geochemical and charcoal data preserved in the Rietvlei wetland. The bulk of the record spans the last 16 ka, but it also provides rare insights into late Marine Oxygen Isotope Stage (MIS) 3 (ca. 35–30k cal a BP). The data suggest that during the Pleistocene the development and permanence of this wetland was probably influenced by sea‐level change via control on the local water table; notably lower sea levels within MIS 2 resulted in very limited wetland productivity. The MIS 3 section provides evidence both supporting previous suggestions of relatively humid conditions, but also some indication of periodic arid phases. The Holocene record suggests clear contrasts between the early (11–7k cal a BP; relatively humid), mid‐Holocene (7–3.3k cal a BP; more arid, less productive wetland conditions) and latest Holocene (last 2k cal a BP; resurgence in both fynbos and aquatic/riparian pollen). While isolating the roles of winter/summer rainfall remains challenging, these data clarify the nature of change during key episodes in the regional palaeoenvironmental record.

Vitamin D-related gene polymorphisms, plasma 25-hydroxyvitamin D, and breast cancer risk - Laura L. Reimers; Katherine D. Crew; Patrick T. Bradshaw; Regina M. Santella; Susan E. Steck; Iryna Sirosh; Mary Beth Terry; Dawn L. Hershman; Elizabeth Shane; Serge Cremers; Elzbieta Dworakowski; Susan L. Teitelbaum; et al. (Cancer Causes & Control, 2015)

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

Lead, Cadmium and Zinc in Hair Samples: Relationship with Dietary Habits and Urban Environment - E. Gonzalez-Reimers; C. Martín-González; L. Galindo-Martín; M. R. Aleman-Valls; J. Velasco-Vázquez; M. Arnay-de-la-Rosa; O. Pérez-Hernández; R. Hernández Luis (Biological Trace Element Research, 2014)

Relative and Combined Effects of Selenium, Protein Deficiency and Ethanol on Hepatocyte Ballooning and Liver Steatosis - E. González-Reimers; M. J. Monedero-Prieto; J. M. González-Pérez; M. C. Durán-Castellón; L. Galindo-Martín; P. Abreu-González; M. J. Sánchez-Pérez; F. Santolaria-Fernández (Biological Trace Element Research, 2013)

Coral-killing cyanobacteriosponge (Terpios hoshinota) on the Great Barrier Reef - T. Fujii; S. Keshavmurthy; W. Zhou; E. Hirose; C. A. Chen; J. D. Reimer (Coral Reefs, 2011)

Chironomid‐inferred late‐glacial summer air temperatures from Lough Nadourcan, Co. Donegal, Ireland - Jenny E. Watson; Stephen J. Brooks; Nicki J. Whitehouse; Paula J. Reimer; H. John B. Birks; Chris Turney (Journal of Quaternary Science, 2010)
Western Ireland, located adjacent to the North Atlantic, and with a strongly oceanic climate, is potentially sensitive to rapid and extreme climate change. We present the first high‐resolution chironomid‐inferred mean July temperature reconstruction for Ireland, spanning the late‐glacial and early Holocene (LGIT, 15–10 ka BP). The reconstruction suggests an initial rapid warming followed by a short cool phase early in the interstadial. During the interstadial there are oscillations in the inferred temperatures which may relate to Greenland Interstadial events GI‐1a–e. The temperature decrease into the stadial occurs in two stages. This two‐stage drop can also be seen in other late‐glacial chironomid‐inferred temperature records from the British Isles. A stepped rise in temperatures into the Holocene, consistent with present‐day temperatures in Donegal, is inferred. The results show strong similarities with previously published LGIT chironomid‐inferred temperature reconstructions, and with the NGRIP oxygen‐isotope curve, which indicates that the oscillations observed in the NGRIP record are of hemispherical significance. The results also highlight the influence of the North Atlantic on the Irish climate throughout the LGIT. Copyright © 2010 John Wiley & Sons, Ltd.

Allelic variation at Psy1-A1 and association with yellow pigment in durum wheat grain - A. Singh; S. Reimer; C. J. Pozniak; F. R. Clarke; J. M. Clarke; R. E. Knox; A. K. Singh (Theoretical and Applied Genetics, 2009)

Long-term ice sheet–climate interactions under anthropogenic greenhouse forcing simulated with a complex Earth System Model - Miren Vizcaíno; Uwe Mikolajewicz; Matthias Gröger; Ernst Maier-Reimer; Guy Schurgers; Arne M. E. Winguth (Climate Dynamics, 2008)

Reindeer (Rangifer tarandus) avoidance of a highway as revealed by lichen measurements - Bjørn Dahle; Eigil Reimers; Jonathan E. Colman (European Journal of Wildlife Research, 2008)

Long-term effects of anthropogenic CO2 emissions simulated with a complex earth system model - Uwe Mikolajewicz; Matthias Gröger; Ernst Maier-Reimer; Guy Schurgers; Miren Vizcaíno; Arne M. E. Winguth (Climate Dynamics, 2007)

Evidence for subdivision within the M molecular form of Anopheles gambiae - M. A. SLOTMAN; F. TRIPET; A. J. CORNEL; C. R. MENESES; Y. LEE; L. J. REIMER; T. C. THIEMANN; E. FONDJO; A. FOFANA; S. F. TRAORÉ; G. C. LANZARO (Molecular Ecology, 2007)
The principal vector of malaria in sub‐Saharan Africa, Anopheles gambiae is subdivided into two molecular forms M and S. Additionally, several chromosomal forms, characterized by the presence of various inversion polymorphisms, have been described. The molecular forms M and S each contain several chromosomal forms, including the Savanna, Mopti and Forest forms. The M and S molecular forms are now considered to be the reproductive units within A. gambiae and it has recently been argued that a low recombination rate in the centromeric region of the X chromosome has facilitated isolation between these forms. The status of the chromosomal forms remains unclear however. Therefore, we studied genetic differentiation between Savanna S, Forest S, Forest M and Mopti M populations using microsatellites. Genetic differentiation between Savanna S and Forest S populations is very low ( F ST = 0.0053 ± 0.0049), even across large distances. In comparison, the Mopti M and Forest M populations show a relatively high degree of genetic differentiation ( F ST = 0.0406 ± 0.0054) indicating that the M molecular form may not be a single entity, but could be subdivided into at least two distinct chromosomal forms. Previously it was proposed that inversions have played a role in the origin of species within the A. gambiae complex. We argue that a possible subdivision within the M molecular form could be understood through this process, with the acquisition of inversions leading to the expansion of the M molecular form into new habitat, dividing it into two distinct chromosomal forms.

The impact of a downslope water-transport parametrization in a global ocean general circulation model - S. Legutke; E. Maier-Reimer (Climate Dynamics, 2002)

A nonlinear impulse response model of the coupled carbon cycle-climate system (NICCS) - G. Hooss; R. Voss; K. Hasselmann; E. Maier-Reimer; F. Joos (Climate Dynamics, 2001)

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Bone trace element pattern in an 18th century population sample of tenerife (Canary islands) - M. Arnay-de-la-Rosa; E. Gonzalez-Reimers; J. Velasco-Vazquez; N. Barros-Lopez; L. Galindo-Martin (Biological Trace Element Research, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Immunological characterization of heterochromatin protein p25β autoantibodies and relationship with centromere autoantibodies and pulmonary fibrosis in systemic scleroderma - Kiyoshi Furuta; Bernhard Hildebrandt; Sayako Matsuoka; Kendo Kiyosawa; Georg Reimer; Christoph Luderschmidt; Edward K. L. Chan; E. M. Tan (Journal of Molecular Medicine, 1997)

Paleodietary analysis on the prehistoric population of El Hierro (Canary Islands) - J. Velasco-V⟹quez; M. Armay-de-la-Rosa; E. González-Reimers; O. Hernández-Torres (Biological Trace Element Research, 1997)

An autonomous. bottom‐transecting vehicle for making long time‐series measurements of sediment community oxygen consumption to abyssal depths - K. L. Smith; R. C. Glatts; R. J. Baldwin; S. E. Beaulieu; A. H. Uhlman; R. C. Horn; C. E. Reimers (Limnology and Oceanography, 1997)
We have developed and successfully collected data with a unique, bottom‐transecting vehicle (ROVER) that permits the first long time‐series measurements of sediment community oxygen consumption (SCOC). This instrument has the following capabilities: (1) it operates as an autonomous, free vehicle on the sea floor to 6,000‐m depth for periods up to 6 months; (2) it transits across the sea floor, minimizing the impact that a long‐term, free‐vehicle structure would have on measurement sites; (3) it measures SCOC by using duplicate benthic chambers at up to 30 different sites over a single deployment period; (4) it measures sediment porewater oxygen concentration as an independent measure of SCOC by using a microprofiler at up to 30 different sites over a single deployment period; (5) it has an incubation period of programmable duration for each SCOC measurement; (6) it monitors operation of instruments and the surrounding area with time‐lapse still and video cameras; (7) it has the flexibility to be used as an autonomous programmable platform for a wide variety of benthic boundary‐layer measurements; and (8) it collects a water sample for oxygen and other analyses at the end of the deployment. The ROVER resembles a small forklift with a forward‐mounted instrument assembly, a current meter, double‐tread propulsion system, central battery and controller electronics, flotation, acoustic releases, and disposable ballast. The ROVER was deployed for a 4‐month period (January–May 1996) to measure SCOC at 4,100‐m depth in the eastern North Pacific. During this deployment the ROVER occupied 17 sites with each benthic chamber incubation lasting 152.3 h and a 17‐h interval between incubations for repositioning and transit. SCOC ranged from 0.50 to 0.91 mmol O 2 n −2 d −1 , generally declining from January until the end of February and then increasing irregularly to the end of the deployment in late May. These measurements show good agreement with those made at the same site with another autonomous instrument, the free‐vehicle grab respirometer, at the beginning and end of the ROVER deployment.